Navigating the stormy seas of inclusion: Educator insights on refugee children in Maltese classrooms through ecological and multicultural lenses - Jacqueline Żammit (Social Sciences and Humanities Open)
The integration of refugee children into early childhood and primary education in Malta presents a complex array of challenges for educators, who must navigate both visible and subtle barriers to create inclusive learning environments. This study offers a novel contribution by combining Bronfenbrenner's Ecological Systems Theory and Critical Multicultural Education to explore the multi-dimensional experiences, challenges, and adaptive strategies of Maltese teachers. Based on 15 in-depth interviews with five educators across three different schools, the study uncovers key themes such as linguistic barriers, social integration, acceptance within peer groups, staffing shortages, teacher competencies, engagement with refugee families, and the navigation of religious and cultural differences. By applying these theoretical frameworks, the study provides an original analysis that connects individual, institutional, and societal factors influencing the integration process. The findings, contextualised within both ecological and multicultural frameworks, not only enhance understanding of the Maltese context but also offer globally relevant insights for educational researchers and practitioners dedicated to fostering inclusive educational practices for refugee children.